2023
DOI: 10.1111/ijfs.16568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzymatic extrusion on the structure and physicochemical properties of oat flour and its application in oat milk production

Abstract: SummaryOat milk has received increasing attention because of its health benefits, however, the problems of easy sedimentation and deterioration of taste during storage are common problems faced by the industry. Enzymatic extrusion is a technology that combines high‐temperature, high‐pressure and high‐shear extrusion with enzymatic hydrolysis for rapid biological transformation of materials. To evaluate the feasibility of enzymatic extrusion to overcome these disadvantages, the effects of this technology on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…This superior foaming capacity was attributed to the higher concentration of native proteins in SFE de-oiled flour, which acted as effective surface-active agents enhancing foam stability through intermolecular forces [22]. Studies reported that defatted soybean cake possessed the highest foaming stability than other leguminous flours [31,32]. Another study compared different oilseed meals of almond, chestnut, hazelnut, pine nut, pistachio nut, and soybean.…”
Section: Sulfhydryl Group Content Surface Hydrophobicity and Protein ...mentioning
confidence: 99%
“…This superior foaming capacity was attributed to the higher concentration of native proteins in SFE de-oiled flour, which acted as effective surface-active agents enhancing foam stability through intermolecular forces [22]. Studies reported that defatted soybean cake possessed the highest foaming stability than other leguminous flours [31,32]. Another study compared different oilseed meals of almond, chestnut, hazelnut, pine nut, pistachio nut, and soybean.…”
Section: Sulfhydryl Group Content Surface Hydrophobicity and Protein ...mentioning
confidence: 99%